Battery negative electrode material as well as preparation method and application thereof
By using composite materials of bismuth phosphate, phosphorus, bismuth and conductive carbon materials in potassium ion batteries, the problems of bismuth anode volume expansion and limited electron transport are solved, the cycle stability and ion diffusion rate of the battery are improved, and the electricity is improved Chemical properties.
Patent Information
- Application Number
- CN202411108940.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-13
AI Technical Summary
During the circulation process, the bismuth anode in potassium ion batteries has large volume changes due to the large K+ ion radius, and the material powdering and electron transport are limited, which affects its electrochemical performance.
Using composite materials containing bismuth phosphate, phosphorus, bismuth and conductive carbon materials as the negative electrode material of the battery, amorphous bismuth phosphate is formed by ball milling, which improves the dispersion and electrochemical properties of the active ingredients, reduces volume expansion, and improves electron conductivity and K+ diffusion.
It improves the cycle stability and ion diffusion rate of the negative electrode material of the battery, enhances the electrochemical performance, reduces the side reaction between the electrode and the electrolyte, and extends the cycle life of the battery.
Smart Images

Figure HDA0004991613200000011 
Figure HDA0004991613200000012 
Figure HDA0004991613200000021
Abstract
Description
Technical Field
[0001] The invention belongs to the field of batteries, and in particular relates to a battery negative electrode material and a preparation method and application thereof. Background Art
[0002] Compared with lithium-ion batteries and sodium-ion batteries (NIBs), potassium-ion batteries (PIBs) have become a promising alternative due to their abundant potassium resources. + / Na(-2.71V), PIBs showed a lower K + / K redox potential (-2.93V), and a small Stokes radius in common electrolytes Therefore, PIBs have the advantage of low production cost and are the main candidate materials for large-scale energy storage systems.
[0003] Recently, bismuth has attracted much attention due to its relatively high theoretical specific capacity, reasonable voltage platform, and cost-effectiveness. In particular, bismuth has a layered crystal structure and semi-metallic conductivity with a large interlayer spacing along the c-axis. This makes it an ideal candidate for anode materials in rechargeable batteries. + Due to the large ionic radius of Bi, the Bi anode undergoes significant volume changes during cycling, leading to material pulverization and continuous side reactions between the electrode and the electrolyte. In addition, the wrinkled layer structure and semi-metallic conductivity of the Bi anode also limit the electron transport and K + Therefore, it is imperative to solve the problem of large volume expansion of Bi anode, improve electronic conductivity and improve K + diffusion to improve its electrochemical performance. Summary of the invention
[0004] In order to overcome the problems existing in the prior art, one of the objectives of the present invention is to provide a battery negative electrode material.
[0005] A second object of the present invention is to provide a method for preparing the above-mentioned battery negative electrode material.
[0006] A third object of the present invention is to provide a battery negative electrode.
[0007] A fourth object of the present invention is to provide a potassium ion battery.
[0008] A fifth object of the present invention is to provide application of the above-mentioned battery negative electrode material and / or battery negative electrode in the battery field.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is:
[0010] The first aspect of the present invention provides a battery negative electrode material, including an active material; the active material is a composite material containing bismuth phosphate, phosphorus, bismuth and a conductive carbon material.
[0011] Preferably, the bismuth phosphate is amorphous.
[0012] Preferably, the bismuth is crystalline.
[0013] Preferably, based on the total mass percentage of the composite material being 100%, the mass percentage of the bismuth phosphate is 20-40%, for example, can be selected from 20%, 25%, 30%, 35%, 40%.
[0014] Preferably, the phosphorus is red phosphorus.
[0015] Preferably, taking the total mass percentage of the bismuth phosphate, the phosphorus and the bismuth as 100%, the mass percentage of the conductive carbon material is 10-30%, for example, 10%, 15%, 20%, 25% or 30%.
[0016] The second aspect of the present invention provides a method for preparing the battery negative electrode material provided in the first aspect of the present invention, comprising the following steps:
[0017] The raw materials of active materials are mixed and then ground to obtain the active materials; the raw materials of active materials include bismuth oxide, phosphorus and conductive carbon material.
[0018] Preferably, the grinding step is performed by ball milling.
[0019] Preferably, the ball milling speed is 100 to 1000 rpm; further preferably, the ball milling speed is 500 to 1000 rpm; further preferably, the ball milling speed is 500 to 900 rpm.
[0020] Preferably, the ball milling time is 1 to 10 h; further preferably, the ball milling time is 4 to 10 h; more preferably, the ball milling time is 6 to 10 h.
[0021] Preferably, the mass ratio of the grinding balls to the raw materials of the active material is (30-40):1.
[0022] Preferably, the ball milling step is performed under the protection of an inert gas.
[0023] Preferably, the inert gas is selected from at least one of nitrogen, xenon and argon.
[0024] Preferably, the molar ratio of bismuth oxide to phosphorus is 1:(0.1-20); further preferably, the molar ratio of bismuth oxide to phosphorus is 1:(0.1-10); further preferably, the molar ratio of bismuth oxide to phosphorus is 1:(1-10); more preferably, the molar ratio of bismuth oxide to phosphorus is 1:(1-3).
[0025] In the present invention, the amorphous bismuth phosphate (BiPO 4 , which is an inactive ingredient) is formed in situ during the ball milling process. Bismuth phosphate can also play a grinding aid role during the ball milling process, reduce the aggregation and regeneration of active ingredients (conductive carbon materials, phosphorus and crystalline bismuth), increase the dispersibility of active ingredients, and help reduce the particle size of active ingredients and improve the utilization rate of active ingredients. In addition, the present invention can solve the volume expansion problem of active ingredients by doping active ingredients with inactive ingredients, improve the huge volume change of battery negative electrode materials during the charge and discharge process, and is beneficial to the stability of SEI film, thereby giving electrode materials better cycle stability.
[0026] Preferably, the bismuth oxide (Bi 2 O 3 The ratio of the total mass of ) and P to the mass of the conductive carbon material is 100:(10-30).
[0027] Preferably, the conductive carbon material comprises at least one of graphite, graphene, carbon nanotubes, carbon nanofibers, carbon nanodots, carbon nanocones, coke, activated carbon, conductive carbon black, and acetylene black. When there are two or more conductive carbon materials, the two or more conductive carbon materials can be mixed in any proportion. Further preferably, the conductive carbon material is selected from at least one of graphite, conductive carbon black, and acetylene black.
[0028] Bismuth, phosphorus and conductive carbon materials form chemical bonds during ball milling to improve the electrochemical properties of the active material, but the resulting composite materials may agglomerate, and the dispersibility is significantly lower than that of the active material doped with bismuth phosphate in the present invention. In addition, amorphous bismuth phosphate can withstand greater volume changes than bismuth in a crystalline structure, and due to its isotropy, it can also promote ion diffusion, which can solve the problem of electrode volume expansion.
[0029] The third aspect of the present invention provides a battery negative electrode, comprising the battery negative electrode material described in the first aspect of the present invention.
[0030] The fourth aspect of the present invention provides a potassium ion battery, comprising the battery negative electrode material described in the first aspect of the present invention; or, the battery negative electrode described in the third aspect of the present invention.
[0031] The fifth aspect of the present invention provides the application of the battery negative electrode material described in the first aspect of the present invention and / or the battery negative electrode described in the third aspect of the present invention in the battery field.
[0032] The beneficial effects of the present invention are as follows: the battery negative electrode material of the present invention can improve the dispersion effect of the conductive carbon material, phosphorus and crystalline bismuth and avoid the occurrence of agglomeration by introducing bismuth phosphate into the active material; on the other hand, bismuth phosphate is an inactive ingredient, and the bismuth phosphate present in the active material can effectively improve the huge volume change during the charge and discharge process, which is beneficial to the stability of the SEI film, thereby giving the electrode material better cycle stability, improving the ion diffusion rate of the battery, and improving the battery cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a flow chart of the preparation process of the battery negative electrode material in Example 1.
[0034] Figure 2 It is the XRD test diagram of the battery negative electrode material in Example 1 and Comparative Examples 1-2.
[0035] Figure 3 This is the SEM image of the battery negative electrode material in Example 1.
[0036] Figure 4 This is the HRTEM image of the battery negative electrode material in Example 1.
[0037] Figure 5 This is the EDS mapping diagram of the battery negative electrode material in Example 1.
[0038] Figure 6 It is the X-ray CT spectrum of the battery negative electrode material in Example 1 and Comparative Examples 1-2.
[0039] Figure 7 This is a thermogravimetric curve test diagram of the battery negative electrode material in Example 1.
[0040] Figure 8 This is a test diagram of the cycle performance of a half-cell formed by Bi@P@BiPO4@C, Bi@P@C, and Bi@C in an embodiment of the present invention.
[0041] Fig. 9 TEM images of the negative electrode materials of the batteries in Example 1 and Comparative Example 1 after 500 charge and discharge cycles.
[0042] Fig.10 X-ray CT spectra of the negative electrode materials of the batteries in Example 1 and Comparative Example 1 before and after cycling.
[0043] Fig.11 The Bi@P@BiPO in Example 1 4@C Schematic diagram of the structure of the assembled full battery.
[0044] Fig.12 The Bi@P@BiPO in Example 1 4 @C Cycling performance test diagram of the full battery formed.
[0045] Fig.13 It is a test diagram of the charge and discharge performance of the battery negative electrode materials in Example 1 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0046] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.
[0047] Example 1
[0048] Reference Figure 1 The preparation flow chart in this example provides a method for preparing a negative electrode material for a battery, and the specific steps are as follows:
[0049] Add the following raw materials into a stainless steel grinding bowl: P (0.11 g) and Bi 2 O 3 (Aladdin, AR, dosage is 0.551g), ball milled at a speed of 800 rpm for 6 hours in an Ar atmosphere to obtain a mixture, then 0.5g of the mixture was taken out and added to a stainless steel grinding bowl, and then 0.1g of conductive carbon black (Super P, based on the total mass percentage of the mixture as 100%, the mass percentage of the conductive carbon black is 20wt%) was added to make the mass ratio of steel ball to powder (i.e., the mixture and Super P) be 40:1, and ball milled at a speed of 800 rpm for 6 hours in an Ar atmosphere to obtain amorphous bismuth phosphate (BiPO 4 )-doped crystalline Bi@P nanocomposite (denoted as: Bi@P@BiPO 4 @C), which is the negative electrode material of the battery in this example. Taking the mass percentage of the negative electrode material of the battery as 100%, the mass percentage of bismuth phosphate is 30wt%.
[0050] Comparative Example 1
[0051] This example provides a method for preparing a negative electrode material for a battery, and the specific steps are as follows:
[0052] The following raw materials were added to a stainless steel grinding bowl: P (in an amount of 0.11 g) and Bi (Aladdin, AR, in an amount of 0.742 g), and ball-milled at a speed of 800 rpm in an Ar atmosphere for 6 hours to obtain a mixture. Then 0.5 g of the mixture was taken out and added to a stainless steel grinding bowl, and then 0.1 g of conductive carbon black (Super P, based on the total mass percentage of the mixture as 100%, the mass percentage of the conductive carbon black is 20 wt%) was added to make the mass ratio of steel ball to powder (i.e., the mixture and Super P) be 40:1. Ball-milled at a speed of 800 rpm in an Ar atmosphere for 6 hours to obtain a Bi@P nanocomposite material (denoted as: Bi@P@C), which is the battery negative electrode material in this example.
[0053] Comparative Example 2
[0054] This example provides a method for preparing a negative electrode material for a battery, and the specific steps are as follows:
[0055] The following raw materials were added to a stainless steel grinding bowl: conductive carbon black (Super P, dosage is 0.1 g, based on the mass percentage of Bi as 100%, the mass percentage of conductive carbon black is 20wt%), Bi (Aladdin, AR, dosage is 0.5 g) 80wt%, so that the mass ratio of steel ball to powder (i.e. Super P and Bi) is 40:1, and ball milling is performed at a speed of 800 rpm in an Ar atmosphere for 6 hours to obtain a Bi nanocomposite material (denoted as: Bi@C), which is the battery negative electrode material in this example.
[0056] Performance Testing
[0057] (1) XRD test
[0058] The XRD data of Bi@P@BiPO4@C, Bi@P@C and Bi@C prepared in Example 1 and Comparative Examples 1-2 were tested by X-ray diffractometer. The specific test results are as follows: Figure 2 As shown. Figure 2 It can be seen that all the diffraction peaks in the XRD curves of Bi@P@BiPO4@C, Bi@P@C and Bi@C correspond to the orthorhombic phase with space group R-3m (JCPDS No.44-1246), and the calculated lattice parameters are and Explanation of the BiPO introduced into Bi@P@BiPO4@C 4 It is amorphous.
[0059] (2) SEM and TEM testing
[0060] The Bi@P@BiPO in Example 1 was tested by scanning electron microscopy. 4 @C's surface morphology, specific test results are as follows Figure 3 As shown, Figure 3 a and Figure 3 b SEM images with scale bars of 2 μm and 200 nm, respectively. Figure 3 It can be seen that in Bi@P@BiPO 4 In the @C sample, the presence of bismuth phosphate prevents the Bi@P particles from densely agglomerating, thereby improving the dispersion and uniformity of the active material during electrode preparation.
[0061] The Bi@P@BiPO in Example 1 was tested by high-resolution transmission electron microscopy (HRTEM). 4 @C HRTEM image, the specific test results are as follows Figure 4 As shown. Figure 4 It can be seen that amorphous red P and Bi crystals exist in the amorphous carbon matrix. 4 In @C composite materials, metallic Bi exists in the form of nanoparticles in the amorphous carbon matrix.
[0062] (3) EDS analysis
[0063] Test Example 1 Bi@P@BiPO 4 @C energy dispersive X-ray spectroscopy (EDS) mapping diagram, the specific test results are as follows Figure 5 As shown by Figure 5 It can be seen that Bi@P@BiPO 4 In the Bi@P@BiPO composites, P, Bi, C and O are evenly distributed. The presence of a small amount of O may be due to 4 @C The composite material is exposed to air, resulting in partial oxidation of P and Bi.
[0064] (4) Microstructure test
[0065] The Bi@P@C in Comparative Example 1 and the Bi@P@BiPO in Example 1 were tested respectively. 4 @C's X-ray CT spectrum, the specific test results are as follows Figure 6 a and Figure 6 As shown in b, Figure 6 The microstructure of Bi@P@C and Bi@P@BiPO4@C at the electrode level can be analyzed. Compared with Bi@P@C, the distribution of Bi@P@BiPO4@C particles is more uniform, which is consistent with the results of scanning electron microscopy.
[0066] (5) Thermogravimetric analysis
[0067] Test Example 1 Bi@P@BiPO 4 @C thermogravimetric curve in air, specific test results are as follows Figure 7 As shown by Figure 7 It can be seen that in Bi@P@BiPO 4 @C, the experimental mass fractions of Bi, P, BiPO 4 and C are 36.33 wt%, 12.6%, 31.7 wt% and 19.37% respectively, which are in good agreement with the theoretical values. From this, it can be known that when synthesizing the Bi@P@BiPO 4 @C composite material, the proposed molar ratio of Bi 2 O 3 to red phosphorus RP can be described as follows:
[0068] 4Bi 2 O 3 +3P = 3BiPO 4 +5Bi
[0069] (6) Battery cycle performance test
[0070] Respectively take Bi@P@BiPO4@C, Bi@P@C, and Bi@C prepared in Example 1 and Comparative Examples 1-2 as active materials, use polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) as binders, and acetylene black as the conductive agent; the mass ratio of the active material, binder, and conductive agent is 7:2:1; make the active material, binder, and conductive agent into a working electrode, use copper foil as the current collector, use potassium metal as the counter electrode, and the electrolyte is a solution of 2.5 mol / L potassium bis(fluorosulfonyl)imide (KFSI) in triethyl phosphate (TEP), assemble into a half-cell, and conduct a cyclic stability test on the half-cell. The test conditions are: constant current charge and discharge, the current density is 0.5 A·g -1 , the voltage range is 0.01 - 3.0 V, and cyclic tests are carried out within this voltage range. The test results are as Figure 8 shown. It can be seen from Figure 8 that the initial specific capacity of Bi@P@BiPO 4 @C in Example 1 is about 340 mA·h·g -1 , and after 1700 cycles, its specific capacity is about 330.0 mA·h·g -1 , with a high capacity retention rate, that is, good cyclic stability, while Bi@P@C in Comparative Example 1 and Bi@C in Comparative Example 2 both have extremely poor cyclic stability.
[0071] Respectively test the TEM images of Bi@P@BiPO 4 @C in Example 1 and Bi@P@C in Comparative Example 1 after charge and discharge cycling 500 times according to the above test conditions. The specific test results are as Fig. 9 a and Fig. 9 b shown. It can be seen from Fig. 9 that after 500 cycles, Bi@P@BiPO in Example 14 The Bi@P@C anode formed a uniform solid electrolyte interface (SEI) with a thickness of about 15 nm, while the Bi@P@C anode in Comparative Example 1 formed an inhomogeneous SEI with a thickness of about 20 to 30 nm. 4 The formation of a uniform SEI on the @C anode is crucial to ensure stable and efficient electrochemical reactions throughout the entire cycle, which can mitigate the adverse effects of side reactions, promote efficient ion transport, and slow down capacity decay.
[0072] The Bi@P@BiPO in Example 1 was tested separately. 4 The X-ray CT spectra of Bi@P@C and Bi@P@C in comparative example 1 before and after 500 charge and discharge cycles according to the above test conditions are as follows: Fig.10 As shown, Fig.10 a and Fig.10 b are Bi@P@C and Bi@P@BiPO respectively 4 @C X-ray CT spectrum before charge and discharge cycles; Fig.10 c and Fig.10 d are Bi@P@C and Bi@P@BiPO respectively 4 @C X-ray CT spectrum after 500 charge and discharge cycles. Fig.10 It can be seen that Bi@P@BiPO 4 @C did not break after 500 charge and discharge cycles, and had the function of adaptive shrinkage. Bi@P@C broke after 500 cycle tests and did not have the function of adaptive shrinkage.
[0073] The Bi@P@BiPO in Example 1 4 @C and commercial 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) were assembled into a full battery (such as Fig.11 Then at 0.1 mA·g -1 The battery performance test results after 100 charge and discharge cycles are as follows: Fig.12 As shown in a. Fig.12 It can be seen that the Bi@P@BiPO in Example 1 4 @C full battery showed good cycling stability at 0.1 mA g -1 After 100 cycles at a current density of 97.83 mA·h·g -1 The discharge capacity of Bi@P@BiPO in Example 1 4 @C The full battery is electrically connected to an electric fan with a power output of 1.0W. The specific physical picture is as follows Fig.12 As shown in b. Fig.12 b It can be seen that the Bi@P@BiPO in Example 14 The full @C cell successfully powered an electric fan with a power output of 1.0 W, confirming the use of Bi@P@BiPO in TEP electrolyte. 4 @C for the practicality.
[0074] Test Example 1 Bi@P@BiPO 4 @C charge and discharge performance, the specific test method is: constant current charge and discharge, the current density is 0.1A g -1 The voltage range is 0.01~3.0V. Cyclic test is performed within this voltage range. The specific test results are as follows Fig.13 a. Test Bi@P@BiPO 4 @C, Bi@P@C and Bi@C. The specific test method is: constant current charge and discharge, the voltage range is 0.01~3.0V, and different current density multipliers are tested within this voltage range. The specific test results are shown in the figure. Fig.13 As shown in b, processing Fig.13 Re-plot the test data in b and get Fig.13 c's test image. Fig.13 It can be seen from a that Bi@P@BiPO 4 The reversible capacity of the @C electrode is as high as 474.3 mA·h·g -1 , the initial coulombic efficiency (ICE) is 61.0%, while the initial coulombic efficiency of Bi@P@C in Comparative Example 1 under the same test conditions is 55.39%, and the initial coulombic efficiency of Bi@C in Comparative Example 2 under the same test conditions is 59.64%. The battery performance of Comparative Examples 1 and 2 is significantly lower than that of Example 1. Fig.13 b It can be seen that in KFSI electrolyte, Bi@P@BiPO 4 @C has better charge and discharge rate capability than Bi@C and Bi@P@C. Fig.13 c shows that at 0.1A·g -1 , 0.2A·g -1 , 0.5A·g -1 and 1.0A·g -1 At a current density of 4 The reversible capacity of @C is 454.6 mA·h·g -1 、417.7mA·h·g -1 、324.9mA·h·g -1 and 188.4 mA·h·g -1 , has good charge and discharge cycle performance.
[0075] In summary, the battery negative electrode material in the present invention can improve the dispersion effect of the conductive carbon material, phosphorus, and crystalline bismuth by introducing bismuth phosphate, and avoid the occurrence of agglomeration; on the other hand, bismuth phosphate is an inactive ingredient, which can effectively improve the huge volume change during the charge and discharge process, which is beneficial to the stability of the SEI film, thereby giving the electrode material better cycle stability, increasing the ion diffusion rate of the battery, and improving the battery cycle performance.
[0076] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A battery negative electrode material, characterized in that: The invention comprises an active material; the active material is a composite material containing bismuth phosphate, phosphorus, bismuth and conductive carbon material.
2. The battery negative electrode material according to claim 1, characterized in that: The bismuth phosphate is amorphous; and / or, the bismuth is crystalline.
3. The battery negative electrode material according to claim 1, characterized in that: Taking the total mass percentage of the composite material as 100%, the mass percentage of the bismuth phosphate is 20-40%.
4. The battery negative electrode material according to any one of claims 1 to 3, characterized in that: Taking the total mass percentage of the bismuth phosphate, the phosphorus and the bismuth as 100%, the mass percentage of the conductive carbon material is 10-30%.
5. The method for preparing the negative electrode material for a battery according to any one of claims 1 to 4, characterized in that: The following steps are involved: The raw materials of the active material are mixed and then ground to obtain; The raw materials of the active material include bismuth oxide, phosphorus and conductive carbon material.
6. The method for preparing a negative electrode material for a battery according to claim 5, characterized in that: The grinding step adopts ball milling, and the ball milling step has at least one of the following characteristics: (a) the ball milling speed is 100 to 1000 rpm; (b) the ball milling time is 1 to 10 hours; (c) The mass ratio of the grinding balls to the raw materials of the active material is (30-40):1; (d) The ball milling step is carried out under the protection of an inert gas.
7. The method for preparing a negative electrode material for a battery according to claim 5, characterized in that: The molar ratio of bismuth oxide to phosphorus is 1:(0.1-20); And / or, the ratio of the total mass of the bismuth oxide and P to the mass of the conductive carbon material is 100:(10-30).
8. A negative electrode of a battery, characterized in that: The negative electrode material of the battery comprises any one of claims 1 to 4.
9. A potassium ion battery, characterized in that: The negative electrode material of the battery comprises any one of claims 1 to 4; or the negative electrode of the battery comprises claim 8.
10. Use of the battery negative electrode material according to any one of claims 1 to 4 and / or the battery negative electrode according to claim 8 in the battery field.
Citation Information
Patent Citations
Composite material for negative electrode of high-performance alkali metal ion battery
CN113479858A
Metal-phosphorus-based negative electrode material with lithium pool storage function and preparation and application thereof
CN116364870A
Composite electrode material, electrode plate, preparation method and application
CN116470016A
Black phosphorus-based composite electrode material and preparation method thereof, black phosphorus-based electrode plate and preparation method and application thereof
CN116706067A
Composite negative electrode material and preparation method and application thereof
CN118263420A
